MODEL SIMULASI TRANSFER HUJAN-ALIRAN PERMUKAAN (MODEL H2U) UNTUK PENDUGAAN DEBIT DAERAH ALIRAN SUNGAISIMULATION MODEL OF RAINFALL-RUNOFF TRANSFER/H2U MODEL FOR CALCULATE DISCHARGE OF WATERSHED - Nani Heryani; Hidayat Pawitan; Gatot Irianto (Agromet, 2002)
Abstract is available in the full text (pdf format)